The CGRP receptor component RAMP1 links sensory innervation with YAP activity in the regenerating liver. Issue 6 (23rd April 2020) - Laschinger, Melanie; Wang, Yang; Holzmann, Gabriela; Wang, Baocai; Stöß, Christian; Lu, Miao; Brugger, Marcus; Schneider, Annika; Knolle, Percy; Wohlleber, Dirk; Schulze, Sarah; Steiger, Katja; et al.
Abstract: The effectiveness of liver regeneration limits surgical therapies of hepatic disorders and determines patient outcome. Here, we investigated the role of the neuropeptide calcitonin gene‐related peptide (CGRP) for liver regeneration after acute or chronic injury. Mice deficient for the CGRP receptor component receptor activity‐modifying protein 1 (RAMP1) were subjected to a 70% partial hepatectomy or repeated intraperitoneal injections of carbon tetrachloride. RAMP1 deficiency severely impaired recovery of organ mass and hepatocyte proliferation after both acute and chronic liver injury. Mechanistically, protein expression of the transcriptional coactivators Yes‐associated protein (YAP) and transcriptional coactivator with PDZ‐binding motif (TAZ) was decreased in regenerating livers of RAMP1‐deficient mice. Lack of RAMP1 was associated with hyperphosphorylation of YAP on Ser127 and Ser397, which regulates YAP functional activity and protein levels. Consequently, expression of various YAP‐controlled cell cycle regulators and hepatocyte proliferation were severely reduced in the absence of RAMP1. In vitro, CGRP treatment caused increased YAP protein expression and a concomitant decline of YAP phosphorylation in liver tissue slice cultures of mouse and human origin and in primary human hepatocytes. Thus, our results indicate that sensory nerves represent a crucial control element of liver regeneration after acute and chronic injury acting through the CGRP‐RAMP1 pathway, which stimulates YAP/TAZ expression and activity.